Relation between body mass index, waist circumference, and death after acute myocardial infarction - Zeller, Marianne; Steg, Philippe Gabriel; Ravisy, Jack; Lorgis, Luc; Laurent, Yves; Sicard, Pierre; Janin-Manificat, Luc; Beer, Jean-Claude; Makki, Hamid; Lagrost, Anne-Cécile; Rochette, Luc; Cottin, Yves (Circulation (New York, N.Y.), 2008)
An elevated body mass index (BMI) has been reported to be associated with a lower rate of death after acute myocardial infarction (AMI). However, waist circumference (WC) may be a better marker of cardiovascular risk than BMI. We used data from a contemporary French population-based cohort of patients with AMI to analyze the impact of WC and BMI on death rates. We evaluated 2229 consecutive patients with AMI. Patients were classified according to BMI as normal, overweight, obese, and very obese (BMI <25, 25 to 29.9, 30 to 34.5, and >35 kg/m(2), respectively) and as increased waistline (WC >88/102 cm for women/men) or normal. Half of the patients were overweight (n=1044), and one quarter were obese (n=397) or very obese (n=128). Increased WC was present in half of the patients (n=1110). Increased BMI was associated with a reduced death rate, with a 5% risk reduction for each unit increase in BMI (hazard ratio, 0.95; 95% CI, 0.93 to 0.98; P<0.001). In contrast, WC as a continuous variable had no impact on all-cause death (P=0.20). After adjustment for baseline predictors of death, BMI was not independently predictive of death. The group of patients with high WC but low BMI had increased 1-year death rate. Neither BMI nor WC independently predicts death after AMI. Much of the inverse relationship between BMI and the rate of death after AMI is due to confounding by characteristics associated with survival. This study emphasizes the need to measure both BMI and WC because patients with a high WC and low BMI are at high risk of death.